STUDI ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT SUKU KAILI IJA DI DESA BORA KECAMATAN SIGI BIROMARU KABUPATEN SIGI SULAWESI TENGAH - Megawati Megawati; Syariful Anam; Ramadhanil Pitopang (Biocelebes, 2016)
The study, entitled "Study of Medicinal Plants Ethnobotany At Tribal Peoples Kaili Ija in Bora village Biromaru Sigi Sigi District of Central Sulawesi" was conducted from March to April 2015. The study aims to obtain information about the kinds of plants and parts used and the way of processing as a traditional medicine. The study was conducted using a combination of quantitative and qualitative methods by interview using the Open-ended interview is free interview techniques or interviews conducted directly using a questionnaire that contains the name of the plant, the type of disease being treated, the plant part used (roots, rhizomes , stems, leaves, flowers, fruits, seeds, tubers, and sap), how to use (taken / eaten, rubbed, smeared, dripped and taped), how processing (crushed, crushed, boiled and crushed) and plant status (wild / aquaculture) with the number of respondents 47 people. The results were obtained 32 types of plants used in traditional medicine by tribal people Kaili Ija. The largest percentage parts used in plants that leaf with a value of 56%.   Keyword : Kaili Ija Ethnic, Bora Village, Sigi, Central Sulawesi, Ethnobotany.